Multiple Micronutrient Supplementation Coverage among Under-two Children in Nafada Local Government Area, Gombe State - Kuma, Lanem Law; Nunghe, Amos Dauda; Bappah, Bashir; Loko, Ekundayo; Nongu, Sesugh; Ayodele, Timilehin; Christiana, Ebun; Adeniyi, Kehinde; Solanke, Ojuolape; Olotu, Joan Oluwafunmilola (Kashere Journal of Politics and International Relations, 2025)
Micronutrient deficiencies remain a significant public health challenge among under-two children in northern Nigeria, contributing to poor growth and developmental outcomes. This study assessed the coverage of multiple micronutrient powder (MNP) supplementation among children under two years in Nafada Local Government Area (LGA), Gombe State—one of three LGAs selected for the Accelerating Nutrition Results in Nigeria (ANRiN) intervention due to its high burden of malnutrition. Utilizing secondary data from the LGA's Health Department Monitoring and Evaluation Unit, we conducted a descriptive analysis of MNP coverage across ten wards. The projected under-two population was estimated at 8% of each ward's total population. This projection was compared with the actual number of children who received MNP during the 2024 intervention period to determine coverage rates. Findings revealed alarmingly low overall MNP coverage (19.4%), with significant disparities between wards—ranging from 0.6% in Birnin Fulani West to 74.7% in Birin Bolawa. Data visualization highlighted stark inequities in program implementation, with remote wards showing particularly poor uptake. The results align with existing evidence on challenges in rural nutrition interventions and underscore systemic barriers in equitable health service delivery. This study emphasizes the urgent need for targeted strategies to improve MNP distribution, particularly in hard-to-reach areas, to effectively address micronutrient deficiencies among vulnerable under-two children in northern Nigeria.